Changes in Lipase and Antioxidant Enzyme Activities during Processing of Cantonese Sausage with D-Sodium Erythorbate - Xiaolan Shang; Jie Qiao; Zhanxiong Chen (Journal of Food Quality)
Pork was used as raw material to produce Cantonese sausage, with additions of 0.05% or 0.1% D-sodium erythorbate. The oxidation indices (peroxide value, TBARS value, carbonyl value, and conjugated dienes value) and enzyme activity (total phospholipase, acid lipase, neutral lipase, superoxide dismutase, and glutathione peroxidase) were measured in the sausages at different processing periods. The results showed slowed lipid oxidation in the presence of D-sodium erythorbate, inhibition of total phospholipase, acid lipase, and neutral lipase activities, and increased superoxide dismutase activity, with little change in glutathione peroxidase activities. When increasing D-sodium erythorbate, the superoxide dismutase activity was negatively correlated with the peroxide value at 5 h (P<0.01), the neutral lipase activity was positively correlated with the conjugated dienes value at 15 h (P<0.01), and the total phospholipase activity was positively correlated with the peroxide value at 30 h (P<0.01). This study explored the antioxidant effect of D-sodium erythorbate and provides a theoretical foundation to improve the quality of Cantonese sausage.